(untitled) - Peters, Tom (New York, 1992)
In the new economy, hierarchical business structures are being consigned to the shredder and replaced with flexible, fast-responding, ad hoc groups of brainworkers. Tom Peters, author of the bestselling IN SEARCH OF EXCELLENCE is once again ahead of the curve, and now demonstrates that the key to success in business future is total engagement, dynamism, speed, and independence...
Keywords: Organizational effectiveness,Hiệu quả tổ chức